2003
DOI: 10.1099/jmm.0.05032-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genotyping of meningococci using a nested PCR approach

Abstract: An effective vaccine against Neisseria meningitidis serogroup B is required. Outer-membrane protein vaccines have been developed, which may provide protection against common circulating serotypes and serosubtypes in some countries. However, limited genosubtyping data are available because most laboratories use mAbs directed against a limited number of specific serotypes and serosubtypes and laboratories do not genosubtype directly from body fluids due to the lack of a sensitive PCR method. A nested PCR was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Permanent sequelae are common among survivors of meningococcal infection (93,95). Definitive diagnosis requires the isolation of N. meningitidis from a normally sterile body fluid or the detection of meningococcal DNA by PCR (36,71,87,259,321).…”
Section: Clinical Aspects Of Meningococcal Infectionmentioning
confidence: 99%
“…Permanent sequelae are common among survivors of meningococcal infection (93,95). Definitive diagnosis requires the isolation of N. meningitidis from a normally sterile body fluid or the detection of meningococcal DNA by PCR (36,71,87,259,321).…”
Section: Clinical Aspects Of Meningococcal Infectionmentioning
confidence: 99%
“…A third variable region, designated VR3, is present on the top of loop V (24). The genetic variability of this region has also been studied previously (1,6,7,10,14,19), and research has revealed a lower level of genetic variability than that found within VR1 and VR2. One potential explanation is that loop V, where VR3 is located, is slightly shorter than loops I and IV, where VR1 and VR2 are located.…”
mentioning
confidence: 99%
“…Volunteers underwent a swabbing from the posterior pharynx (i.e., soft palate and pillars) performed by a trained physician. Swabs were immediately plated on chocolate agar supplemented with vancomycin, colimycin and amphotericin B (VCAT agar, Biomérieux, France) and incubated at 35-37 • C under 7.5% CO 2 for 48 h. Meningococci were detected and identified by standard methods (colony morphology with one to three colonies from each morphotype, Gram stain, oxidase, biochemical profile using API-NH strip [Biomerieux, France]) and by PCR targeting ctrA and porA genes [12,13]. Isolates were characterized by genogrouping, serogrouping, serotyping, serosubtyping, and sequence typing by multilocus sequence typing (MLST) [14].…”
Section: Carriage Studymentioning
confidence: 99%